Efficacy of Sedentary Time Reduction with Mobile Texting and Focused Educational Sessions in Patients with Coronary Artery Disease: a Randomized Controlled Trial - W, Deeprasertdamrong; P, Swanpitak; N, Sanjaroensuttikul; P, Uaaree; K, Kobkitsumongkol; S, Sangmanee; S, Ratvijitwech; T, Chaianansin (ASEAN Journal of Rehabilitation Medicine, 2020)
Objectives: To assess the efficacy of mobile texting and focused educational session on sedentary behavior in patients suffering from coronary artery disease. Study design: Randomized controlled trial. Setting: Cardiac Rehabilitation Clinic, Rehabilitation Medicine Department, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, Thailand. Subjects: Patients with coronary artery disease who underwent cardiac rehabilitation program from November 2018 to May 2020 at Ramathibodi Cardiac Rehabilitation Clinic. Methods: The participants were randomized to receive either a standard cardiac rehabilitation (control group), or a standard cardiac rehabilitation with mobile texting and focused educational sessions on sedentary behavior (intervention group). Seden-tary time and time spent in other physical activity levels were recorded at baseline, 1, 3, and 6 months following participation in both groups. This was done using the Thai short International Physical Activity Questionnaire (Thai short IPAQ). The effects of mobile texting and focused educational sessions on sedentary behavior were analyzed by employing a mixed effects linear regression analysis. Results: Participants spent about 13.72 hours/day engaging in sedentary behavior. The intervention group showed significantly less prevalence of diabetes compared with the control group. This baseline difference was adjusted in the regression model. The between-group comparison study found that sedentary time was significantly less at 3 months in the intervention group compared with the control group (at 3 months; difference 1.75 hour/day, p = 0.002). Mild intensity physical activity rose signi-ficantly only at the end of the study (at 6 months; difference 1.00 hour/day, p = 0.047). There was no significant difference between the two groups at all follow-up intervals for moderate-to-vigorous physical activity. Conclusion: Additional mobile texting and focused educational sessions on sedentary behavior to a standard cardiac rehabilitation program, helped the patients with coronary artery disease reduce their sedentary time at 3 months.